PERKAWINAN ADAT DI MALUKU: ANTARA ADAT, PENDIDIKAN DAN AGAMA (STUDI KASUS TERHADAP KELUARGA MUSLIM DI JAZIRAH LEIHITU DAN KECAMATAN SIRIMAU MALUKU) - Sri Wahyuni (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2022)
This article discusses about custom of marriage in Maluku, especially in muslim family at Jazirah Leihitu and Sirimau district, in line of education, custom and religion aspects. The research shows that education, custom, and religion in the Maluku muslim society, especially in Jazirah Leihitu and Sirimau district, each has influence to the custom of marriage. The level of education becomes a determinant of marriage cost which a man must give it to his girl. The plurality of custom in Sirimau which is in Ambon city also has influence in changing the customary marriage, although the Maluku custom must be obeyed by the migrant society there. Religion also has little influence to the customary marriage, but the custom is more dominant. For the example is concept of marriage cost is more dominant than mahr in the society.